So we died : a memoir of life and death in the Ghetto of Šiauliai, Lithuania - Shalit, Levi (2025)
"So We Died (Azoy zaynen mir geshtorbn)" is a translation from the Yiddish of a powerful eyewitness account of life in the Shavl (Šiauliai, Lithuania) ghetto from 1941 to 1944. For two-and-a-half years, 5,000 Jews were confined in the ghetto in Shavl/Šiauliai, Lithuania's third biggest city, which is located between Kovno/Kaunas to the south and Riga, Latvia, to the north. In contrast to other key European ghettos, few documents survive from the Shavl ghetto. Three accounts of the Shavl ghetto years exist, yet to date none has been published in English. Among these accounts, Levi Shalit's stands out for its power, beauty, and vision. Shalit was a true literary stylist who sought to convey the story of the ghetto with nuance and vibrancy. He was an acute psychological observer who wrestled with profound questions about the human condition. His work offers unique insights into the motivations, the inner and outer conflicts, and the desperate challenges facing his community.